El lado oscuro del mercado inmobiliario en Duitama: una mirada al fraude y las estafas - Garzón Ávila, Laura Camila (Universidad Antonio Nariño, 2023)
The real estate scam is an unfair practice that has affected thousands of people around the world, generating significant economic losses, including Duitama. In this article, article 251.1 of the penal code will be addressed which simplifies real estate crime from different perspectives with the aim of providing a comprehensive view of this financial fraud, will investigate existing laws and regulations in Colombia to protect property buyers from all real estate scam activities. In addition, a description will be made of the different tactics used by the scammers and present precautionary measures to protect an investment and thus avoid falling into the traps of the scammers.